Systems serology analysis shows IgG1 and IgG3 memory responses six years after one dose of quadrivalent HPV vaccine - Chau Quang; Jeremy Anderson; Fiona M. Russell; Rita Reyburn; Tupou Ratu; Evelyn Tuivaga; Rachel Devi; Ian H. Frazer; Suzanne M. Garland; Bruce Wines; P. Mark Hogarth; Kim Mulholland; et al. (Nature Communications)
Abstract The WHO has given a permissive recommendation for an off-label one-dose human papillomavirus (HPV) vaccine schedule to prevent cervical cancer, based on evidence of comparable protection to two or three doses of vaccine. While neutralizing antibodies are thought to be the primary mechanism of protection, the persistence of immunity and whether other antibody-mediated mechanisms of protection are involved is unclear. Using systems serology, we investigated HPV antibody responses in serum from Fijian girls who were unvaccinated or received one, two or three doses of quadrivalent HPV vaccine six years earlier. We also evaluated their HPV antibody responses 28 days following a dose of bivalent HPV vaccine. After six years, one dose induced lower antibody concentrations but similar antibody profiles and phagocytic function as two or three doses. Following bivalent vaccine, antibody concentrations, particularly IgG1/IgG3, antibody profiles and phagocytic function were similar between previously vaccinated girls, indicating immune memory after one dose. Cross-reactive antibody responses against non-vaccine genotypes (HPV31/33/45/52/58) were lower following one dose than two or three doses. These findings provide novel insights into serological immunity and recall responses following one-dose HPV vaccination.